2003
DOI: 10.1590/s0100-204x2003000600015
|View full text |Cite
|
Sign up to set email alerts
|

Reação de cultivares de soja a isolado de Curtobacterium flaccumfaciens pv. flaccumfaciens, proveniente de feijoeiro

Abstract: , and MG/BR-48 (Garimpo RCH) to a strain of Curtobacterium flaccumfaciens pv. flaccumfaciens, isolated from common bean, using two inoculation methods, in greenhouse. All soybean cultivars showed low level of susceptibility to the bacterial strain, independently of the inoculation method used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…SYN1163RR was previously planted, although studies have shown the capacity of Cff to cause disease in soybean in Brazil (Soares et al 2013). Studies showed that different levels of resistance can exist between cultivars of soybean against Cff, from susceptibility to higher levels of resistance (Bracale and Soares 2014;Maringoni and Souza 2003). This could explain the reason for the lower recovery of Cff when common bean was rotated with soybean cv.…”
Section: Discussionmentioning
confidence: 99%
“…SYN1163RR was previously planted, although studies have shown the capacity of Cff to cause disease in soybean in Brazil (Soares et al 2013). Studies showed that different levels of resistance can exist between cultivars of soybean against Cff, from susceptibility to higher levels of resistance (Bracale and Soares 2014;Maringoni and Souza 2003). This could explain the reason for the lower recovery of Cff when common bean was rotated with soybean cv.…”
Section: Discussionmentioning
confidence: 99%
“…Neste experimento, o enraizamento do sapotizeiro mostrou a formação de dois tipos distintos de raízes, uma mais grossa e comprida, comum em todas as estacas enraizadas e outra mais fina e curta obtida em algumas estacas (Figura 1). Em virtude desta peculiaridade, optou-se pela avaliação qualitativa, através da escala de notas, como os relatados por Cornélio et al (2000) e Maringoni e Souza (2003).…”
Section: Resultsunclassified
“…Differences in virulence observed during inoculation by different strains may be associated with variability of the complex system of regulation of virulence factors. For example, it has been shown that strains isolated from common bean were weakly virulent for soybean, but that inoculation with the same strains re-isolated from soybean showed strong virulence against soybean [ 28 ].…”
Section: Discussionmentioning
confidence: 99%